MENINGKATKAN KEMAMPUAN KOGNITIF MELALUI PEMANFAATAN MEDIA PEMBELAJARAN DIGITAL BAAMBOOZLE PADA KELOMPOK B DI TK ABA WASUR II - Retno Wuri Sulistyowati; Mega Suteki (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
The purpose of this study is to improve cognitive abilities through the use of digital learning media Baamboozle in group B at Kindergarten Aba Wasur II Merauke which will be held in the even semester of the 2021/2022 academic year. The subjects in this study were the children of Aba Wasur II Merauke Kindergarten, totaling 11 students consisting of 5 girls and 6 boys with an age range of 5-6 years. Based on the analysis of the teacher's teaching activity data in the first cycle, it reached 78.61%. Cycle one children's learning activities reached 71.47%. The learning outcomes of students in improving cognitive abilities through digital learning media Baamboozle in cycle one reached 54.58%. Cycle two shows that the analysis of teacher teaching activities has increased to 92.9%. The second cycle of children's learning activities experienced an increase of 92.9%. Based on the learning outcomes of students in improving cognitive abilities through digital learning media Baamboozle in cycle two it reached 90.9%. Thus it can be concluded that cognitive abilities can be improved through digital learning media Baamboozle in group B at TK Aba Wasur II Merauke.